Seeing the woods for the trees: the problem of information inefficiency and information overload on operator performance - Dadashi, Nastaran; Golightly, David; Sharples, Sarah (2016)
One of the recurring questions in designing dynamic control environments is whether providing more information leads to better operational decisions. The idea of having every piece of information and increasing situation awareness is so tempting (and in safety critical domains often mandatory) that has become an obstacle for designers and operators. This research examined this challenge within a railway control setting. A laboratory study was conducted to investigate the presentation of different levels of information (taken from data processing framework, Dadashi et al., 2014) and the association with, and potential prediction of, the performance of a human operator when completing a cognitively demanding problem solving scenario within railways. Results indicated that presenting users with information corresponding to their cognitive task (and no more) improves the performance of their problem solving/alarm handling. Knowing the key features of interest to various agents (machine or human) and using the data processing framework to guide the optimal level of information required by each of these agents could potentially lead to safer and more usable designs.